SARS coronavirus infections of the lower respiratory tract and their prevention - Petrovsky, N. (The Microbiology of Respiratory System Infections, 2016)
The Severe Acute Respiratory Syndrome (SARS) coronavirus was first identified in 2003 when it caused an epidemic of fatal human pneumonia cases that rapidly spread to multiple countries from an epicenter in Hong Kong. The outbreak was eventually controlled by quarantine measures but not before it had caused many fatalities. The original zoonotic source of the SARS virus that caused the outbreak is still unknown but is suspected to be bats. Attempts were made to develop a prophylactic vaccine but the SARS epidemic was over before any vaccines could be tested for human efficacy. As will be discussed in this chapter, coronavirus vaccines present many challenges including low and rapidly waning immunity and the fact that coronavirus vaccines, particularly when formulated with Th2-biased alum adjuvants, can exacerbate coronavirus infection-associated eosinophilic lung immunopathology. Fortunately, this problem can be avoided by formulation of coronavirus vaccines with Th1-type adjuvants that enhance T cell IFN-γ responses, such as, delta inulin or TLR agonists. Hence, appropriate adjuvant selection is vitally important for the development of safe and effective coronavirus vaccines. This chapter will describe the current state of development of SARS vaccines, the issue of coronavirus-associated eosinophilic lung immunopathology and how adjuvants can be used to reduce the risk of this complication.